Carbon contamination of soft X-ray beamlines dramatic anti-reflection coating effects observed in the 1 keV photon energy region - Chauvet, C (Journal of synchrotron radiation, 2011)
Carbon contamination is a general problem of under-vacuum optics submitted to high fluence. In soft X-ray beamlines carbon deposit on optics is known to absorb and scatter radiation close to the C K-edge (280 eV), forbidding effective measurements in this spectral region. Here the observation of strong reflectivity losses is reported related to carbon deposition at much higher energies around 1000 eV, where carbon absorptivity is small. It is shown that the observed effect can be modelled as a destructive interference from a homogeneous carbon thin film